2015
DOI: 10.1016/j.biocon.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Climate change threatens giant panda protection in the 21st century

Abstract: a b s t r a c tIt is increasingly recognized that biotic interactions could play a significant role in species distribution modelling. To assess the conservation effectiveness of the giant panda (Ailuropoda melanoleuca) reserves in a changing climate, we combined both biotic variables (food availability) and abiotic (climatic and geographic) to project the potential changes of distribution and quality of giant panda habitats using the most recent IPCC-CMIP5 climate scenarios. Our results suggested that climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 57 publications
1
51
2
Order By: Relevance
“…5). A recent study on the whole giant panda distribution area suggested that the mean patch size of habitats would decrease from the current 652 ha to 531 ha, and the most severe fragmentation would drive the mean patch size of the habitats decreased by 30% (Li et al, 2015). The decreased mean patch size (451 ha) of the habitat in the whole giant panda distribution area would not be smaller than the extinction threshold area 400 ha under future climate changes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…5). A recent study on the whole giant panda distribution area suggested that the mean patch size of habitats would decrease from the current 652 ha to 531 ha, and the most severe fragmentation would drive the mean patch size of the habitats decreased by 30% (Li et al, 2015). The decreased mean patch size (451 ha) of the habitat in the whole giant panda distribution area would not be smaller than the extinction threshold area 400 ha under future climate changes.…”
Section: Discussionmentioning
confidence: 98%
“…Other recent studies of the entire giant panda distribution area showed that 53-71% of the current habitats would be lost under the climate scenarios. They predict that future suitable habitats would likely be located in high-elevation areas in the Min Shan and Liang Shan (Li et al, 2015), and the suitable habitat gradually moves north under projected global climate change (Jian et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species with limited geographic ranges, small population sizes, and habitat specializations are especially vulnerable to rapidly changing climate which may increase the risk of extinction for some taxa (Castro de la Guardia et al 2013;Li et al 2015). Identifying the specific aspects of climate change that affect population sizes and trends is a first but critical step in the assessment of how climate change will influence population persistence.…”
Section: Introductionmentioning
confidence: 99%
“…These SDMs, which rely on ecological theory of processes that mediate species distributions and abundance -especially niche theory (Guillera-Arroita et al 2015), are currently the main approach for converting individual point-locality data, such as museum collection records (Loiselle et al 2003;Peterson et al 2011) into the potential distributional range of a species or predicted ranges following global climate change (Li et al 2015). Thus, SDMs have the potential to play a critical role in supporting spatial conservation decision making, especially when conservation biologists are often pressed to make recommendations about conserving biodiversity based on limited species-distribution data and biodiversity resources (Addison et al 2013).…”
Section: Introductionmentioning
confidence: 99%